(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Throughout the day we spend time with our colleagues at the workplace. We used to communicate with each other and transfer our thoughts, feelings, emotions and experiences. After analyzing the schedule of the whole day it has been observed that we use language to communicate but most of the time without spoken words we convey messages effectively just with the help of some cues, expressions and symbols. It proves that humans can communicate with language or without language. When we communicate with language it is called verbal communication and when we communicate with any other medium other than language that appeals to our senses and information is transferred between two individuals we can call it nonverbal communication. People give importance to verbal communication at the workplace but most of the time they neglect the importance of nonverbal communication. Nonverbal communication is an important aspect of the 21st century as it lays emphasis on behavior of an individual at his place of work. Interpreting and analyzing information are keys in understanding messages but most of the time interpreting nonverbal cues is a big challenge. This paper will focus on various aspects of nonverbal communication which are playing a vital role at the workplace.